(untitled) (Fiep Bulletin - online, 2015)
Stress is a symptom that tends to interfere with the performance of people who practice physical activities of a competitive nature in different forms or periods of his life.The objective of this study was to determine the level of anxiety and stress in professional dancers of urban dance in pre-competitive phase of 32 Joinville dance festival.Investigative protocol analysis of the level of stress on the individual who has applied for dancers who participated in the competitive exhibition of the 32nd festival of dances of Joinville was used,totaling 102 subjects of both sexes and of different ages, 52 (50.98%) males and 50 (49.02%) women with a mean age of 21.36 ± group 3.74 years, with a minimum age of respondents 16 years and maximum 37 years.The evaluation protocol was used to measure the degree of anxiety and stress, STAI - State-Trait Inventory Anxiety formulated by Spielberger et al. (1970) translated by Natalício and Biaggio (1979) for the Brazilian population. Of the subjects, 53% had levels of anxiety and 47% median level of very high state anxiety.On trait anxiety, 85% had median level of total and 15% very high level.From the data collected, it is noticed that in competitive events is the common presence of stressors that in turn can evoke emotional responses as well as changes in the behavior of the participants.To better compete, the dancer needs to have a good physical preparation and also needs to have a good intellectual preparation, in other words, paying special attention to the psychological element.By understanding the behavior of the competitive event participant shall be able to work on the elements that constitute the decisive factor to the result,in other words, motivation and performance.